Durable life assessment of centrifugal stratified PHC piles in marine environment. (15th July 2022) - Wang, Hui; Chen, Haohua; Yang, Changyi; Li, Jingpei
Highlights: Durable life assessment for open- and closed-ended PHC pipe piles. The open-ended pile with a thinner mortar layer has a longer durable life. Closing the end of the pile is the most effective way to lengthen the life span. Abstract: This study proposes an analytical approach to assess the durable life of pre-stressed high-strength concrete (PHC) pipe piles exposed to the marine environment with consideration of centrifugal stratification and different end types. The durable life of the PHC pile is divided into two stages: the initiation stage for chloride penetration and the propagation stage for rust accumulation. To simulate the two stages, a two-layer composite cylinder diffusion model and a thick-walled ring mechanical model are developed based on the governing mechanisms. The proposed diffusion model is verified via comparisons with the numerical models with respect to chloride concentration under different stages. Then, extensive parametric studies based on the proposed method are performed to investigate the effects of end type, cover thickness, and steel bar diameter on the durable life of a PHC pipe pile. The results indicate that both increasing the cover thickness and using the closed-ended pile can significantly extend the durable life of a PHC pipe pile. Furthermore, the open-ended pile with a thinner mortar layer has a longer durable life, while the durable life of a closed-ended pile only slightly increases with a larger thickness of the mortar layer.